Stay or discontinue? Examining the drivers and inhibitors of continuance usage intention toward TRING! Pegadaian - Tarysha Aulya Putri Rany; Henny Firizqi (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: The rapid digitalization of financial services has encouraged financial institutions to develop mobile-based platforms that enhance service accessibility, operational efficiency, and customer convenience. As part of this transformation, Pegadaian introduced TRING!, a digital financial application that integrates various financial services into a single platform. Despite its growing adoption, limited studies have examined the factors influencing users’ intention to continue using digital financial applications in the post-adoption stage. This study aims to investigate the drivers and inhibitors of continuance usage intention toward TRING! by Pegadaian by integrating enabling and inhibiting factors within the framework of Resistance Theory. Methods: A quantitative research design was employed using a cross-sectional online survey of 128 TRING! users in Indonesia. Data were collected through a structured questionnaire measured on a five-point Likert scale and analyzed using PLS-SEM. Findings: The results reveal that network externalities and trust positively and significantly influence continuance usage intention, indicating that users are more likely to continue using TRING! when they perceive strong social adoption and have confidence in the application's security and reliability. Conversely, the unavailability of facilitating conditions negatively affects continuance usage intention, suggesting that inadequate technical support and infrastructure remain important barriers. In contrast, performance expectancy, perceived risk, and operational constraints were found to have no significant influence on continuance usage intention. Conclusion: The findings demonstrate that users’ continuance intention is influenced not only by perceived benefits but also by contextual barriers that emerge after technology adoption. These results support the applicability of Resistance Theory in explaining post-adoption behavior within digital financial services. Practically, Pegadaian should strengthen user trust, expand network value, and improve facilitating conditions to encourage sustained application usage. Novelty/Originality of this article: This study extends Resistance Theory by integrating both enabling and inhibiting factors to explain continuance usage intention toward a state-owned digital financial application in Indonesia, offering a more comprehensive perspective on post-adoption behavior in digital financial services.